Maternal trajectories of cannabis use and young adult cannabis and nicotine dependence. (March 2022) - De Genna, Natacha M.; Goldschmidt, Lidush; Richardson, Gale A.; Day, Nancy L.
Graphical abstract: Highlights: Cannabis use during and after pregnancy is increasing among women. Patterns of maternal cannabis use predicts cannabis use in offspring. Adult cannabis use and CUD is predicted by chronic maternal cannabis use. Chronic maternal cannabis use also predicts nicotine dependence in offspring. Abstract: Introduction: The goals of this study were to model maternal patterns of cannabis use from one year pre-pregnancy to 16 years postpartum and to determine if different patterns of maternal cannabis use predicted offspring substance use at age 22. Methods: Women were recruited from a prenatal clinic between 1982 and 1984. Maternal cannabis use was assessed by trained interviewers twice during pregnancy, at delivery, 8 and 18 months, 3, 6, 10, 14, and 16 years postpartum. At age 22, substance use and dependence were measured in offspring. Growth mixture models of maternal cannabis use were calculated and adult offspring substance use outcomes were regressed onto maternal cannabis trajectory classes (n = 551). Results: There were five distinct patterns of maternal cannabis use. Offspring of mothers who were chronic cannabis users were more likely to use cannabis (p < 0.001) and develop CUD (p < 0.05) than offspring whose mothers did not use cannabis. Offspring of chronic cannabis users were also more likely to be nicotine dependent by age 22 than offspring whose mothers did not use cannabis (p < 0.01) and than offspring whose mothers were decreasingly likely to use over time (p < 0.01). Conclusions: Integrated variable- and person-centered analyses revealed long-term and meaningful patterns of cannabis use and desistance. Chronic maternal cannabis use is a risk factor for regular and dependent cannabis use and for dependent tobacco use among young adult offspring. These findings have implications for maternal-child health given the increasing prevalence of cannabis use among women.